Motivational interviewing for social anxiety disorder: An examination of the technical hypothesis. (17th February 2021) - Romano, Mia; Arambasic, Jelena; Peters, Lorna
ABSTRACT : Background and objective : Motivational interviewing (MI) was originally developed to treat problematic drinking but is increasingly integrated into treatment for anxiety disorders. A causal model has been proposed which suggests technical and relational factors may account for the efficacy of MI. The technical hypothesis suggests that therapist MI-consistent behaviours are related to client change talk, and change talk is linked to treatment outcome. Research examining the technical hypothesis has typically been conducted in MI for substance use; therefore, the current study aimed to explore the technical hypothesis in MI for social anxiety disorder (SAD). Method : Participants diagnosed with SAD ( n = 85) each received MI prior to receiving group cognitive-behavioural therapy (CBT). MI sessions were coded for behaviours relevant to the MI technical hypothesis. Results : The proportion of MI-consistent therapist behaviours and reflections of change language significantly predicted the proportion of change talk by the client during MI sessions; however, therapist and client behaviours did not predict treatment outcome. Conclusion : The findings support one path of the MI causal model in the context of social anxiety, though indicate that the occurrence of these behaviours during an MI pre-treatment may not extend to predict treatment outcome following CBT.